Motion of Elastic Particles and Spectrum of Hydrogen Atoms (Global Journal of Science Frontier Research, 2019)
This article analyzes the spectral structure of hydrogen atoms according to the motion theory of elastic particles. The results demonstrate that optical radiation originates from the elastic vibration of atoms or molecules. The quantum state is the equilibrium feature of the classically statistical system, and the quantum transition is the process of conversion between different motion modes.
Keywords: spectral structure of hydrogen atoms